2015
DOI: 10.1177/1012690215609786
|View full text |Cite
|
Sign up to set email alerts
|

Twelve not so angry men: Inclusive masculinities in Australian contact sports

Abstract: Sport's utility in the development of a conservative orthodox ideal of masculinity based upon homophobia, aggression and emotional restrictiveness, is well evidenced in critical masculinities scholarship. However, contemporary research is reflecting a more nuanced understanding of male behaviour in many Western contexts, with men performing softer and more inclusive versions of masculinities. Through exploring the experiences of twelve Australian contact sport athletes, this research establishes findings to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Boys [in sports] learn early that to be gay, to be suspected of being gay, or even to be unable to prove one’s heterosexual status is not acceptable.” Anderson (2002) described team sports as an arena in which “hegemonic masculinity is reproduced and defined, as an athlete represents the ideal of what it means to be a man, a definition that contrasts to what it means to be feminine and/or gay” (p. 860). More recent research suggests these attitudes are changing, with an associated decrease in homophobia in sport (Anderson, 2011a; Bush et al, 2012), including in Australia (Murray & White, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Boys [in sports] learn early that to be gay, to be suspected of being gay, or even to be unable to prove one’s heterosexual status is not acceptable.” Anderson (2002) described team sports as an arena in which “hegemonic masculinity is reproduced and defined, as an athlete represents the ideal of what it means to be a man, a definition that contrasts to what it means to be feminine and/or gay” (p. 860). More recent research suggests these attitudes are changing, with an associated decrease in homophobia in sport (Anderson, 2011a; Bush et al, 2012), including in Australia (Murray & White, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Like men of the 1980s, they make friends through sports, drinking, and video games, but unlike men of the 1980s, however, they also shop, dine, vacation, and sleep together (Anderson 2014). They also maintain the opportunity to form deep emotional relationships, based on emotional disclosure with one another (Murray and White 2015). Whereas Bank and Hansford (2000) previously found that male friendships struggle due to emotional restraint, masculine hierarchies and homophobia, many scholars now suggest that that the millennial generation has promoted a culture that is much more inclusive and cohesive (Adams 2011;McCormack 2012;Thurnell-Reid 2012).…”
Section: Contrasting 20mentioning
confidence: 99%
“…On the question of changes being made, some researchers have been arguing that a “soft masculinity” is now being found in such places as Australian football, where homophobic masculinity is on the decline, and with it the need for men to forcefully and vocally act hyper-masculine to prove to themselves and others that they are not homosexual (Murray & White, 2017). There have been similar findings of reduced homophobia in other observations (Morris & Ratajczak, 2019), but the question remains as to whether these behaviors are real behavioral and attitudinal changes that must be accounted for or superficial changes that allow men to look progressive while at the same time enabling these same men to both reap and promote the advantages of gender privilege (Bridges & Pascoe, 2014).…”
Section: Is the Problem Being Reduced?mentioning
confidence: 99%